THE EFFECT OF QUENCHING WITH VARIOUS COOLING MEDIA ON THE HARDNESS OF LEAD SCREW PIN IN A LATHE MACHINE - Muhammad Rizki Akbar; Fenoria Putri; Baiti Hidayati (Yayasan Amanah Nur Aman, 2026)
This study analyzes the effect of the quenching process with various cooling media on the hardness of lead screw keys in a lathe. The objective was to determine the most effective cooling media for improving the key's mechanical properties, which play a critical role in the performance and durability of the lead screw. The cooling media tested included water, fresh SAE 10W-40 oil, and used SAE 10W-40 oil. The research method involved heat treatment at 850°C, followed by quenching using each medium, and then testing the hardness using the Rockwell B (HRB) method. The results revealed an unexpected finding: the untreated key had the highest hardness value (97.05 HRB), surpassing all quenched samples. Among the hardened samples, water produced the highest hardness (91.88 HRB), followed by used oil (82.32 HRB) and fresh oil (78.66 HRB). This indicates that the quenching process did not increase hardness and, in some cases, even decreased it. Potential causes include temperature instability during heat treatment and inaccurate material characterization, as SEM analysis failed to confirm the expected composition of the high-carbon steel. This study concluded that the quenching parameters and material characterization methods require refinement. Future research is recommended to utilize more precise temperature control, validate the material composition using techniques such as Optical Emission Spectroscopy (OES), and explore alternative cooling media. These findings emphasize the importance of precise heat treatment process control to achieve desired mechanical properties in industrial applications.